Hvorledes kom Grundtvig til at oversætte Saxo og Snorre? - Johansen, Steen (Grundtvig-studier, 1968)
How did Grundtvig Become a Translator of Saxo and Snorri?By Steen Johansen.The treatise is occasioned by the appearance, one hundred and fifty years ago, of the first part of Saxo’s History of Denmark and Snorri Sturlason’s History of Norway (Heimskringla) in Grundtvig’s translation.In 1809 Paul Amesen, senior schoolmaster in Christiania, suggested to Selskabet for Norges Vel the idea of publishing a translation of Heimskringla done by himself; but against the wishes of the society the plan did not include the poems of the work. Finally Grundtvig was agreed upon as the most suitable translator and he took the task upon him. The period in question lay at the centre of his Bible Christian phase; for a while he contemplated Christianizing his version of “Håkonarmål”, but gave up the idea.When Amesen withdrew, Grundtvig became sole translator, and about New Year’s day 1815 , under the impression of the separation of Norway from Denmark, it occurred to him that he might publish the work of Saxo as well as of Snorri as a confirmation of the spiritual connection between the two countries. The idea was stimulated also by the belief of the Romantic poet that “through a devoted study of antiquity its glory could be and should be born again”.